Exploring the antinociceptive potential of homoeriodictyol in nociception models - Manal H. Al-Bzour; Yousra Bsieso; Omar Gammoh; Mohammed Alqudah; Esam Y. Qnais; Mohammed Wedyan; Abdelrahim Alqudah (GarVal Editorial Ltda., 2024)
Context: Homoeriodictyol is a flavonoid with known antioxidant, anti-inflammatory, and anti-tumor properties found in various plants. However, its potential analgesic effects have not been explored. Aims: To investigate the pain-relieving properties of homoeriodictyol using different mouse models of nociception. Methods: Various doses of homoeriodictyol (50, 100, 150, and 200 µg/kg) were administered to mice and evaluated using the acetic acid-induced writhing test, the hot plate test, and the formalin-induced paw licking assay. These effects were compared with those of mice treated with acetylsalicylic acid or morphine, both with and without naloxone, an opioid receptor antagonist. Additionally, capsaicin- and glutamate-induced paw-licking tests were conducted to assess the involvement of the vanilloid and glutamatergic systems, respectively. Results: Homoeriodictyol demonstrated a significant and dose-dependent reduction in nociceptive behavior in the acetic acid-induced writhing test, achieving a 52.4% inhibition at a dose of 200 µg/kg. It also substantially increased the latency period in response to the hot plate test (65.8% at 200 µg/kg) and significantly suppressed both the neurogenic and inflammatory phases in the formalin-induced paw-licking test. Notably, the effects of homoeriodictyol in the hot plate test and formalin-induced paw-licking test were significantly reversed by naloxone. Furthermore, homoeriodictyol effectively reduced neurogenic nociception induced by intraplantar injections of glutamate and capsaicin (57.8% and 76.9%, respectively, at a dose of 200 µg/kg). Conclusions: This study concludes that homoeriodictyol exhibits antinociceptive activity in mice, acting through both central and peripheral pathways.